Keputusan Pembelian Ditinjau dari Kualitas Produk dan Harga Melalui Kepuasan Pelanggan sebagai Variabel Intervening Pada Produk MS GLOW Official Store Sukorejo - Aprilia, Sintya; Susilowati, Heni (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
Skin care beauty products are increasingly becoming a trend among Indonesian people. The high interest in facial care products attracts local manufacturers to produce them. One of the beauty products, namely MS GLOW, is a skincare product where this local product is very popular among teenagers and adults. This research aims to determine the influence of product quality and price on purchasing decisions as well as customer satisfaction as intervening variables. The total population is MS Glow skincare customers in Sukorejo and the sample used was 45 customers using a simple random sampling technique. The research results show that product quality and price have a positive and significant effect on purchasing decisions. Meanwhile, customer satisfaction is not proven to mediate the relationship between product quality and price on purchasing decisions.